Substance Use Disorders in Men Presenting to a Psychosexual Clinic. (6th January 2014) - Rajkumar, Ravi Philip
Abstract : Introduction . Substance use disorders (SUDs) are commonly associated with a variety of psychiatric disorders. Community-based studies have found a significant association between SUDs and sexual dysfunction in men, with a possible causal relation in the case of nicotine. Methods . The case records of 105 men presenting to a clinic for patients with psychosexual disorders were reviewed. Men with and without comorbid SUDs were compared in terms of demographic, clinical, and familial variables. Results . 25 of the 105 men (23.8%) had a lifetime diagnosis of SUD, and 19 (18.1%) had a current SUD. The commonest substances involved were nicotine ( n = 21, 20%) and alcohol ( n = 9, 9.5%). Men with comorbid SUDs were more likely to report a family history of substance dependence, particularly alcoholism. Single men with SUDs were more likely to have a comorbid mood disorder. Conclusion . SUDs, particularly nicotine and alcohol use disorders, are common comorbidities in patients with psychosexual disorders. Identifying and treating these disorders in this population are important aspects of management.